2014
DOI: 10.1002/ana.24256
|View full text |Cite
|
Sign up to set email alerts
|

Spreading depression in continuous electroencephalography of brain trauma

Abstract: Leão's spreading depression can be observed in clinically standard, continuous scalp EEG, and underlying depolarizations can spread widely across the injured cerebral hemisphere. These results open the possibility of monitoring noninvasively a neuronal pathophysiological mechanism in a wide range of disorders including ischemic stroke, subarachnoid hemorrhage, and brain trauma, and suggest a novel application for continuous EEG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 40 publications
6
68
0
1
Order By: Relevance
“…It has been shown that the negative DC shifts of SD can be detected with scalp DC‐EEG,33, 59 although important ambiguities remain and further research is needed to develop a reliable technique. In the case of abrupt ischemia, recordings might be particularly complicated by large BBB‐generated DC potentials due to p ti O 2 and p ti CO 2 changes 49, 50.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the negative DC shifts of SD can be detected with scalp DC‐EEG,33, 59 although important ambiguities remain and further research is needed to develop a reliable technique. In the case of abrupt ischemia, recordings might be particularly complicated by large BBB‐generated DC potentials due to p ti O 2 and p ti CO 2 changes 49, 50.…”
Section: Resultsmentioning
confidence: 99%
“…On this basis, non-invasive technologies to measure rCBF and its surrogates and cEEG should be further advanced to broaden the availability of information on SDs from non-surgical patient populations (Drenckhahn et al, 2012;Hartings et al, 2014). A caveat to consider though is that non-invasive technologies alone are not yet sufficient to reliably diagnose SDs.…”
Section: Discussionmentioning
confidence: 99%
“…Only in the last two decades, subdural ECoG recordings in patients and measurements in brain slices provided unequivocal electrophysiological evidence that SDs do occur in the human brain (Avoli et al, 1991;Dohmen et al, 2008;Dreier et al, 2006Dreier et al, , 2009Fabricius et al, 2006;Hartings et al, 2011aHartings et al, , 2011bMayevsky et al, 1996;Strong et al, 2002). SD's correlates in the scalp EEG were identified with simultaneous recordings of subdural ECoG and continuous scalp EEG (cEEG) (Drenckhahn et al, 2012;Hartings et al, 2014), and animal studies revealed that the propensity to SD markedly declines in Neuron 86, May 20, 2015 ª2015 Elsevier Inc. 913 Neuron Review the course of epileptogenesis (Kö hling et al, 2003;Maslarova et al, 2011;Tomkins et al, 2007).…”
Section: The Clinical Correlates Of Sustained Depolarizationsmentioning
confidence: 99%
“…The long-term functional significance of this surprising lability of dendritic spine morphology to cognitive function, and future susceptibility to a range of pathologies from Alzheimer's to epilepsy to migraine, is unknown. However, it seems a reasonable hypothesis that the complete recovery of spine size at their former locations following SD that is promoted by GLYX-13 is likely to be therapeutically beneficial in preventing long-term negative sequelae of migraine, and other generators of SDs such as traumatic brain injury (Hartings et al, 2009(Hartings et al, , 2014Sword et al, 2013), ischemia (Risher et al, 2010) and seizures (Takano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%